A Study on Morphometry and Morphological Variation of Suprascapular Notch in Dried Human Scapula - Sudarshan Gupta; Zarna Patel; Deepak Howale (International Journal of Anatomy Radiology and Surgery, 2017)
Introduction: The Suprascapular Notch (SSN) is located at the superior border of the scapula, just medial to the base of the coracoid process. The knowledge of variations in shapes and dimensions can be helpful to clinicians to correlate the suprascapular nerve entrapment with a specific type of notch. Aim: This study was carried out to observe morphological variation in shapes of SSN and morphometric analysis of SSN. Materials and Methods: A total of 120 adult scapulae of unknown age and sex will be obtained from Department of Anatomy, GMERS Medical College, Gandhinagar and Sola, Gujarat, India. The shapes of SSN were observed and dimensions were taken by digital Vernier caliper. Results: The most common type of SSN observed was Type 2, a notch that was longest in its transverse diameter. The least common type was Type 4. Type 5 SSN was absent. The most common shape was ‘J’ and least common was ‘V’.Partial and complete ossification was also noted. Conclusion: Knowledge of anatomical variations of suprascapular notch is better for understanding location and source of entrapment syndrome. Since, the present study is performed with a limited number of dry scapulae, so there is need of further clinical, radiological and cadaveric studies.